O pescador artesanal do baixo São Francisco e a efetividade do direito humano e fundamental ao trabalho - Brito, Henrique Magno Oliveira de (2018)
The present research aims to analyze the effectiveness of the right to work of artisanal fishermen from the lower São Francisco. The causes and obstacles to the effectiveness of human rights is reflected from the theoretical contributions of Joaquim Herrera Flores (2009), Boaventura de Sousa Santos (2002) and Oscar Vilhena Vieira (2017) and the reflection of ineffectiveness of contemporary work in the world. The work of the artisanal fisherman is examined, specifically the characteristics present in the way of life of these workers, the panorama of the baixo São Francisco, and the consequences of the economic development applied to the region through the construction and operation of hydroelectric. Thus, the central problem investigated in this study is the following question: In the view of artisanal fishermen from the baixo São Francisco, is the effectiveness of the fundamental human right to work hampered by the environmental damages caused by the construction of the hydroelectric along this river? It is established as hypothesis that the operation of the set of CHESF hydroelectric has hindered the effectiveness of the fishermen's right to work, and the national development policy promotes the overlapping of the economic interests of the ruling classes to the detriment of the environmental protection interests of the river and social protection of artisanal fishermen work in the region. With regard to the methodology, it is an exploratory research. Their procedures are bibliographic, documentary and field study with the application of interviews, which accompany all stages of research development.